New Methods in Human Resources Management - Ibragimova, Yuliya; Khelerová, Vladimíra, 1961-; Vojtíšek, Zdeněk; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This diploma thesis concentrates on relationship between employee satisfaction and usage of new methods in Human Resources Management, particularly coaching and talent management. As employee satisfaction becomes one of the most important sources of influence on company's performance, it is also discussed in the theoretical background the relationship between employee satisfaction and company performance. The goal of the thesis is to find relationship between usage of new HRM methods (coaching and talent management) and employee satisfaction. The thesis has four chapters. First two chapters "Measurement Systems in an Organization" and "Methods in HR Management" set a theoretical background for the research. The third chapter concentrates on the research itself: employees of five Russian companies both with and without coaching and talent management, are tested. In the last chapter are compared research outcomes and theoretical approach, as well as, recommendations are given.
Vedoucí práce: Vladimíra Khelerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses